THE ROLE OF NUTRITION IN DENTAL CARIES - Shaykhova, G.I.; Zokirkhonova, Sh.A.; Nortaeva, N.A. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
The article provides data on nutrition for dental caries: the importance of food and nutrients: proteins, fats, carbohydrates, minerals and vitamins, as well as prevention of dental caries